Changes in intracellular folate metabolism during high-dose methotrexate and Leucovorin rescue therapy in children with acute lymphoblastic leukemia - Oosterom, Natanja (PLoS One, 2019)
BACKGROUND: Methotrexate (MTX) is an important anti-folate agent in pediatric acute lymphoblastic leukemia (ALL) treatment. Folinic acid rescue therapy (Leucovorin) is administered after MTX to reduce toxicity. Previous studies hypothesized that Leucovorin could ‘rescue’ both normal healthy cells and leukemic blasts from cell death. We assessed whether Leucovorin is able to restore red blood cell folate levels after MTX. METHODS: We prospectively determined erythrocyte folate levels (5-methyltetrahydrofolate (THF) and non-methyl THF) and serum folate levels in 67 children with ALL before start (T0) and after stop (T1) of HD-MTX and Leucovorin courses. RESULTS: Erythrocyte folate levels increased between T0 and T1 (mean ± SD: 416.7 ± 145.5 nmol/L and 641.2 ± 196.3 nmol/L respectively, p<0.001). This was due to an increase in 5-methyl THF levels (mean increase: 217.7 ± 209.5 nmol/L, p<0.001), whereas non-methyl THF levels did not change (median increase: 0.6 nmol/L [-9.9–11.1], p = 0.676). Serum folate levels increased between T0 and T1 (median increase: 29.2 nmol/L [32.9–74.0], p<0.001). Results were not significantly affected by age, sex, ALL immunophenotype and MTHFR c.677C>T genotype. CONCLUSION: Intracellular folate levels accumulate after HD-MTX and Leucovorin therapy in children with ALL, suggesting that Leucovorin restores the intracellular folate pool. Future studies are necessary to assess concomitant lower uptake of MTX.